Evaluación de la bioaumentación de Trichoderma y Azotobacter como alternativa de manejo en el cultivo de mandarina (Citrus reticulata), luego de la poda de renovación - Guerra Cuichan, Luis Eduardo (2023)
The presence of microorganisms in the soil is essential for the sustainable increase of agricultural systems\; they inhabit the rhizosphere of the earth. They are multifunctional, that is, they can be symbiotic, nitrogen fixers, synthesize secondary metabolites, etc. It covers species of fungi, viruses and bacteria. The general objective of this research was to evaluate the effect of soil application of Trichoderma spp. and Azotobacter spp. in the absorption of nutrients and leaf development, in the cultivation of mandarin after renewal pruning. Regarding the methodology, a completely randomized block design was used, with 3 treatments plus a control, each experimental unit was composed of 4 mandarin trees\; Variables such as the 19 19 physicochemical properties of the soil, number and length of shoots, and foliar analysis were evaluated. Among the results obtained for soil chemical factors, the best treatment was T3 (Trichoderma spp. + Azotobacter spp.) with values of: nitrogen 56.4 ppm, phosphorus 149.43 ppm, potassium 2.69 meq/100 ml, organic matter 4.21%, and pH 6.5, with respect to the number and length of shoots, an average of 45.33 shoots and 22.77 cm respectively was obtained. When compared with the control (T4), nitrogen was obtained at 30.5 ppm, phosphorus 72 ppm, potassium 0.75 meq/100 ml, matter organic 3.34%, and pH 6.65 and in terms of number of shoots, 19.17 and shoot length 9.49 cm were obtained. The research highlights the fascinating interaction between microorganisms, minerals and organic matter. By incorporating microorganisms into the soil during the cultivation of mandarin (Citrus reticulata) and applying renewal pruning, a notable improvement in nutrient absorption is achieved. This significant advance promises to substantially optimize the agricultural process.